A Study on Awareness of Chronic Obstructive Pulmonary Disease (COPD) Among Smokers - Nilay N Suthar; Khushali L Patel; Jainam Shah (Medsci Publications, 2015)
Background: COPD is the disease characterized by chronic airway obstruction and it is not fully reversible. As per the WHO's estima- tion, COPD will become 3rd common cause of the death by 2020. It is very essential to study awareness about COPD among smokers. So, we conducted this study with following aims and objectives. Objectives: The objective of this study was to observe the COPD awareness level in smokers and study the factors influencing smok- ing. Methods: Current smokers aged 18 to 59 belonging to the areas of west zone, Ahmedabad were recruited after a verbal informed con- sent using pre-validated Questionnaire. Results: The study included 230 participants. Participants were ob- served as: very less aware = 3.47% (8); less aware = 26.95% (62); aver- age aware = 51.73% (119); good aware = 16.52% (38); very good aware = 1.30% (3). 60% of the smokers felt cough, 23% felt chronic mucus production, 13% felt shortness of breath and 12% felt wheezing. Conclusion: Very low level of awareness is seen in the population who are in current smokers. About half of the participants were not even 50% aware of the COPD.